2023
DOI: 10.3389/fgene.2022.873884
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CKAP2L expression in patients with clear cell renal cell carcinoma

Abstract: Background: Cytoskeleton-associated protein 2-like protein (CKAP2L) is thought to promote the progression of glioma, breast cancer, and ovarian cancer. However, the role of cytoskeleton-associated protein 2-like protein in clear cell renal cell carcinoma (ccRCC) is still unclear. The study aimed to investigate the roles and mechanisms of cytoskeleton-associated protein 2-like protein in clear cell renal cell carcinoma.Methods: The level of cytoskeleton-associated protein 2-like protein in tumors was explored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In one study, it was suggested that its knockdown induces cell cycle arrest in the G2/M phase. In addition, since CKAP2L is correlated with numerous immune checkpoint inhibitor genes, it could indirectly affect immune system functions, thus favoring ccRCC development [ 152 ].…”
Section: Novel Strategiesmentioning
confidence: 99%
“…In one study, it was suggested that its knockdown induces cell cycle arrest in the G2/M phase. In addition, since CKAP2L is correlated with numerous immune checkpoint inhibitor genes, it could indirectly affect immune system functions, thus favoring ccRCC development [ 152 ].…”
Section: Novel Strategiesmentioning
confidence: 99%